Superconductor thermohydraulical and resistive electrical analytical model (STREAM) applied to WEST TF coil quench analysis. (July 2022) - Nicollet, S.; Torre, A.; Lacroix, B.; Louzguiti, A.; Gorit, Q.; Team, WEST
Highlights: Superconductor thermohydraulical & resistive electrical analytical model -STREAM. New CEA developed tool and application for WEST toroidal field coil quench. Thermohydraulic analysis for magnets cooled in superfluid helium bath (0D model). Benchmarking with measurements and calculated SuperMagnet model results. Significant gain (execution time) for forced flow cooled CICC magnets safe operation. Abstract: The Toroidal Field (TF) system of the WEST tokamak comprises 18 NbTi superconducting coils, cooled in a static superfluid helium bath at 1.8 K and carrying a nominal current of 1255 A. The 19th December 2017, at the end of plasma run #52205, a quench of TFC09 was detected, first on a thermohydraulical signal (helium liquid level), and triggered the current Fast Safety Discharge (FSD). The quench was found to be induced by a neutron and gamma flux caused by highly energetic runaway electrons (30 MeV) colliding the outboard plasma facing components. Some previous analyses with SuperMagnet (CryoSoft) code confirmed a so called "smooth" quench with small initial heat deposition length (0.4 m) at low field region (external leg) and with a number of initially quenched conductors nearly equal to 100. A Superconductor Thermohydraulical and Resistive Electrical Analytical Model (STREAM) has been developed. This model comprises the electrical equations (magnetic field, current sharing temperature, quenched length evolution, Joule energy, resistive voltage, resistance and current) and a thermodynamical and an hydraulical evolutions in two following sequences. The first one comprises the helium pressure evolution with an isentropic compression (closed volume) of a cold volume by a hot (and heated) volume; the second one comprises the determination of expulsed helium mass flow in the exhaust circuit (from a given pressure threshold) with a limit at atmospheric pressure or Mach number equal to 1. The whole TFC09 circular coil is modelled by a single bath with one conductor of length equal to coil average perimeter. For WEST TFC09 quench STREAM calculations, the inputs are the Minimum Quench Energy (MQE) and the propagation law of the quenched (normal) length. Calculated STREAM results showed good agreement with the measurements as well as the calculated SuperMagnet results. The maximal resistive voltage, Joule energy and resistance are respectively at 1400 V, 18 MJ and 5 Ω. The maximal values of helium pressure, conductor temperature and expulsed helium mass flow are respectively 0.9 MPa, 80 to 90 K and 4 to 5 kg/s. This STREAM analytical model can be useful (with adaptation to CICC configuration) for other tokamak magnets safe operation and protection, notably considering that the execution time is rather small due to the set of solved equations.